Nisan Tanpa Keadilan: Menelisik Tragedi Kanjuruhan Yang Belum Menemukan Titik Terang - Nadia Nadia; Imroatuth Thoyyibah; Fitriana Ashari; Laela Kurnia Nafitasari; Didi Pramono (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Humans in their lives have many interests and goals, so it is inevitable that conflicts and quarrels may occur due to conflicting interests. The Kanjuruhan tragedy was a bloody conflict that claimed hundreds of lives, which was caused by many factors, one of which was the difference in interests that led to abuse of authority. One of the main problems according to the community's perspective in the Kanjuruhan phenomenon was the firing of tear gas by the police. The police at that time became stewards by complying with all the regulations set by FIFA and at the same time had a role as law enforcers and obeyed the laws in force in Indonesia. For this reason, this article aims to discuss how the Kanjuruhan incident occurred, through the analysis of Dahrendorf's conflict perspective theory and how the Authority at that time played its role. This article is prepared with a research method using a qualitative approach, namely the literature study method and analysis of the Watchdoc Documentary Youtube channel.